Ivermectin-related adverse clinical events in patients treated for Mansonella ozzardi infections - Krolewiecki, Alejandro Javier (2011)
We report the occurrence of serious reactions after treatment with oral ivermectin in two patients with Mansonella ozzardi infections. Both had systemic and respiratory symptoms and recovered without sequelae. Follow-up revealed clearance of microfilaremia in both cases, with relapse in one of them. These reactions are well described in the treatment of other filarial infections, but have not yet been reported in the treatment of M. ozzardi. We are now reporting the first such known reactions with this helminthiasis.